Multiple Stakeholder Perspectives on Teletherapy Delivery of Speech Pathology Services in Rural Schools: A Preliminary, Qualitative Investigation - Michelle Lincoln; Monique Hines; Craig Fairweather; Robyn Ramsden; Julia Martinovich (International Journal of Telerehabilitation)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 12pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The objective of this study was to investigate stakeholders’ views on the feasibility and acceptability of a pilot speech pathology teletherapy program for children attending schools in rural New South Wales, Australia. Nine children received speech pathology sessions delivered via Adobe Connect® web-conferencing software. During semi-structured interviews, school principals (n = 3), therapy facilitators (n = 7), and parents (n = 6) described factors that promoted or threatened the program’s feasibility and acceptability. Themes were categorised according to whether they related to (a) the use of technology; (b) the school-based nature of the program; or (c) the combination of using technology with a school-based program. Despite frequent reports of difficulties with technology, teletherapy delivery of speech pathology services in schools was highly acceptable to stakeholders. However, the use of technology within a school environment increased the complexities of service delivery. Service providers should pay careful attention to planning processes and lines of communication in order to promote efficiency and acceptability of teletherapy programs.